2013
DOI: 10.12659/msm.889526
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with nursing after surgery due to cervical or lumbar discopathy

Abstract: BackgroundRelationships between patient satisfaction with nursing and patient clinical data have not been fully resolved in a Polish sample. Our objectives were to determine clinical factors associated with patient satisfaction with nursing and investigate differences between patients treated surgically for cervical or lumbar discopathy and degenerative changes.Material/MethodsThis prospective and cross-sectional study included 63 consecutively selected patients treated surgically for lumbar discopathy and deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Degenerative disc disease (DDD) is one of the most frequently encountered conditions in everyday clinical practice resulting in chronic back and neck pain, spinal instability and inevitably in functionality impairment [ 1 , 2 ]. The diminution of quality of life and depressive illness are some of the common findings among patients with DDD [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Degenerative disc disease (DDD) is one of the most frequently encountered conditions in everyday clinical practice resulting in chronic back and neck pain, spinal instability and inevitably in functionality impairment [ 1 , 2 ]. The diminution of quality of life and depressive illness are some of the common findings among patients with DDD [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported by Gelalis, et al, (2010) (36) in the study about "prospective analysis of surgical outcomes in patients undergoing decompressive laminectomy and posterior instrumentation for degenerative lumbar spinal stenosis" who stated that over than half of the patients in the study weren't receiving any type of conservative measures. Additionally, Garczyk, et al, (2013) (37) in the study of patient satisfaction with nursing after surgery due to cervical or lumbar discopathy, they mentioned that around one third of patient with lumbar surgery didn't receive any physiotherapy prior to operation. Concerning body mass index; the findings indicated that over than half of the patients in the study were overweight or obese.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical interventions have been found to restore function, decrease pain, and enhance quality of life in properly selected patients with lumbar degenerative diseases [ 3 ]. Posterior lumbar interbody fixation and fusion after decompression is the standard method used to treat lumbar degenerative diseases.…”
Section: Discussionmentioning
confidence: 99%